Cutaneous involvement as the initial presentation of metastatic breast adenocarcinoma - Case report - Verônica Riquet de Siqueira; Aline Salmito Frota; Israel Leitão Maia; Hercília Maria Carvalho Queiroz; Jose Telmo Valença Júnior; José Wilson Accioly Filho (Sociedade Brasileira de Dermatologia, 2014)
Cutaneous metastasis is an uncommon manifestation of visceral malignancy. It occurs late in the course of the disease but can be a sign of an unknown neoplasm. A case of local cutaneous metastasis by contiguity with breast adenocarcinoma is reported. It presented as initial manifestation and main complaint of a 68-year-old woman, with no family history and negative screening tests for the disease. Biopsies of ulcers which do not heal, persistent hardened erythema and cutaneous nodules of unknown cause must be performed, since the evidence of cutaneous metastasis can be of extreme importance for the diagnosis, staging and prognosis of an internal cancer. In this scenario, the dermatologist plays a fundamental role and should be always attentive to this diagnostic possibility.